A prospective study of simultaneous myomectomy with cesarean section at a tertiary care hospital - Sharma, Medhavi; Sharma, Gaurav; Varshney, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Simultaneous surgical removal of a previously diagnosed myoma during cesarean section is preferred these days to reduce multiple operative procedures. The aim of present study was to determine the safety, cost effectiveness and complications of myomectomy at the time of cesarean delivery and its related peri-operative morbidity. Methods: This prospective study was conducted in total 50 pregnant cases during the period of 6 months. The analysis focused on age and gender, the number, size and location of fibroids, the need for hysterectomy and blood transfusion. Results: The mean age of patient was 28.2 years. Out of the 50 patients, 66% were primiparous and only 17% were multiparous. 56% patients underwent caesarean section for indications like primigravida head floating, IUGR, oligohydroaminos. 48% patients had myoma size 2-4 cm. Most of the myomas were located anteriorly (64%). The most common type of leiyomyoma found was subserosal (31%) and 17% with intramural fibroid. Only one patient required post operative blood transfusion whereas none of the patients underwent hysterectomy. Conclusions: Cesarean myomectomy is a safe and effective procedure and it is a feasible undertaking in experienced hands.